Expectation Identities of Generalized Order Statistics from Marshall-Olkin Extended Uniform Distribution and its Characterization - Athar, Haseeb; Nayabuddin (Journal of statistical theory and applications, 2015)
The Marshall-Olkin extended uniform distribution is introduced and studied by Jose and Krishna (2011). In this paper some moments properties of generalized order statistics (gos) for this distribution are investigated and results are deduced for order statistics and record values. In the last section, a characterization result is presented.